The Memory of the Varilongo Mine (Santa Comba) - Blanco Ramos, Carmen (Madrygal. Revista de Estudios Gallegos, 2020)
The objective of this work is to emphasize the importance of memory of the protagonists in the research work on tungsten in the Varilongo mine, in the Santa Comba town hall (Blanco Ramos 2016). Faced with the absence of written sources, it was the memory of the workers who filled the different gaps during World War II.